2017
DOI: 10.1155/2017/7501807
|View full text |Cite
|
Sign up to set email alerts
|

Autologous and Nonautologous Blood Transfusion in Patients with Ruptured Ectopic Pregnancy and Severe Blood Loss

Abstract: Background There are some theoretical concerns for the use of intraoperative cell salvage (ICS) in patients with ectopic pregnancy. This study aimed to observe the impact of ICS on the coagulation function and clinical outcomes of patients with ruptured ectopic pregnancy and severe blood loss. Methods This was a retrospective study of 225 patients with ruptured ectopic pregnancy and severe blood loss treated at the Third Affiliated Hospital of Guangxi Medical University between January 2012 and May 2016. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Rudra and Basak [31] reported 1 patient who underwent IOCS and experienced intraoperative coagulopathy during major obstetric hemorrhage. Postsurgical thrombin time and prothrombin time have been reported to be lower in some IOCS subgroups in patients with ectopic pregnancy, [32] while the infusion rate of coagulation components was consistently higher in IOCS groups in this study. It was difficult to judge whether the increase of thrombin time and prothrombin time was caused by the use of IOCS or by the different coagulation component infusion rates.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Rudra and Basak [31] reported 1 patient who underwent IOCS and experienced intraoperative coagulopathy during major obstetric hemorrhage. Postsurgical thrombin time and prothrombin time have been reported to be lower in some IOCS subgroups in patients with ectopic pregnancy, [32] while the infusion rate of coagulation components was consistently higher in IOCS groups in this study. It was difficult to judge whether the increase of thrombin time and prothrombin time was caused by the use of IOCS or by the different coagulation component infusion rates.…”
Section: Discussionmentioning
confidence: 47%
“…The duration of postoperative hospital stay was significantly shorter in the IOCS group, suggesting that IOCS resulted in good clinical outcomes. Huang et al [32] reported that cell salvage transfusion did not lead to adverse reactions or complications and resulted in shorter hospitalization stay. Studies comparing cell salvage with ABT have found increased oxygen delivery efficacy and mean erythrocyte viability in salvaged blood.…”
Section: Discussionmentioning
confidence: 99%
“…Once significant peritoneal hemorrhage is identified during intervention, and homologous blood transfusion is the most prompt and established way to achieve cardiovascular stability, which is necessary for the treatment of the causative disorder [3]. On the other hand, homologous blood transfusion may be associated with potential risks, including transfusion reactions caused by blood mismatch, and the transmission of blood-borne infections, including human immunodeficiency viruses, hepatitis viruses, and prions [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, such morbidities have usually been managed by laparotomy, occasionally with homologous blood transfusion if necessary [3]. Along with progress in laparoscopic surgical techniques and expertise, improvement in perioperative management of hemodynamic condition by anesthesiologists has facilitated minimally invasive surgical management by laparoscopy for women experiencing hemodynamic instability due to ectopic pregnancy even with massive hemoperitoneum [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%